Working Group on Bycatch of Protected Species (WGBYC) ... - ICES (ICES Scientific Reports, 2025)
February 2025 (minor correction): List of authors were updated. The Working Group on Bycatch of Protected Species (WGBYC) was established in 2007 and collates and analyses information from across the Northeast Atlantic and adjacent sea areas (Baltic, Mediterranean, and Black Seas) related to the bycatch in commercial fishing operations of protected and sensitive species including marine mammals, seabirds, turtles, and sensitive fish species.WGBYC seeks to describe and improve understanding of the likely impacts of fishing activities on affected populations, to inform on the suitability of existing at-sea monitoring programmes for assessing sensitive species bycatch, and to collate information on bycatch mitigation efforts.The report provides an overview of data collection activities during 2023 including details of reported monitoring and fishing effort data, and bycatch records that were submitted to the WGBYC database in 2024 following a formal data call (ToR A). Data were requested from 17 of the 20 ICES ...